On the issue of planning and preparation of Petsamo-Kirkenes offensive operation in Arctic - A. V. Shaidorov (Омский научный вестник: Серия "Общество. История. Современность")
The article reveals the issues of preparation of the Petsamo-Kirkenes offensive operation on October 7–29, 1944. Based on the study of domestic and foreign literature, an analysis of the prerequisites, stages of the operation at the time of its planning, as well as the features of the use of troops at the beginning of the operation is presented. The composition of the forces and means of the opposing sides is revealed. The tasks of the parts at the initial stage of the operation are disclosed.